Employers' policies and attitudes towards the performance of older employees in Lithuania - Daiva Skučienė; Julija Moskvina (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The ageing labour force is the one of the main challenges for the labour market in Lithuania. The working career of older employees very much depends on the policies and attitude of employers. Thus, the aim of this paper is to analyse the policies and attitudes of Lithuanian employers towards older employees. The data of Eurobarometer 76.2 in 2011 and the data of the employers' survey in Lithuania in 2014 were used for the implementation of the goal. The construction, trade, education, health care and public administration sectors were selected on arbitrary basis. The respondents were surveyed by telephone. The sample of the survey included 216 managers or staff managers. The employers in primary data of Eurobarometer 76.2 were defined as general and middle managers. The data were analysed using the method of factor analysis. The secondary Eurostat data were used for the analysis of socioeconomic context. The legal norms were analysed using national documents. The main findings of the research reveal the general positive attitude of employers towards older workers in Lithuania. However, the existing workplace practice gives little encouragement for prolonging the working career in older age due to obsolete cultural and legal norms.
Keywords: D91; J14; J26; M54; 650; employers; old age; employees; attitudes; characteristics